Rivers of the Ganga-Brahmaputra-Meghna Delta A Fluvial Account of Bengal - Rudra, Kalyan (Geography of the Physical Environment,, 2018)
This is the first comprehensive book on the rivers of the Ganga-Brahmaputra-Meghna delta. This volume covers all aspects of this highly populated region including land conflicts and environmental impacts such as the Indo-Bangladesh conflict over sharing of trans-boundary water. This book addresses the topic from a highly interdisciplinary perspective covering areas of geography, geology, environment, history, archaeology, sociology and politics of the Bengal region. The book appeals to a wide range of audiences from India, Bangladesh and the international community. The style of presentation makes it easily suitable for students, researchers and interested laymen. .